Demographic and Clinical Features and Factors Associated with Survival in Patients with Primary Glomerulonephritis: Single Tertiary Center Experience - Nail PAKSOY; Sinan TRABULUS; Nurhan SEYAHİ; Mehmet Rıza ALTIPARMAK (Namık Kemal Tıp Dergisi, 2023)

(untitled)
Aim:Primary glomerulonephritis (GN) is a rare disease that has many different subtypes and is a significant health problem. Patients with primary GN (PGN) often do not achieve a complete cure, typically require immunosuppressive therapy, and can have serious co-morbidities due to the disease, which often progresses to end-stage renal disease (ESRD). The current study aimed to investigate the epidemiological, clinicodemographic characteristics and long-term outcomes of PGN patients.Materials and Methods:The current study retrospectively evaluated the demographic characteristics and complaints as well as the physical examination and laboratory findings of PGN patients who were followed-up and treated in the nephrology department of our university hospital between January 2000 and June 2016.Results:Of the 485 included patients, 265 were male (55%) and 220 were female (45%). The median age at diagnosis was 38.5 years (range; 18-77). The most frequent indication for biopsy was nephrotic syndrome (53.2%). The most common histopathological diagnoses were IgA nephritis (33.2%), focal segmental GN (31.1%), and membranous GN (19.6%), respectively. It was observed that male gender (p=0.01), systemic hypertension (p=0.01) at the time of diagnosis, proteinuria (p=0.001) in the nephrotic range, and histological diagnosis of crescentic GN (p=0.001) contributed negatively to renal survival. The mean follow-up duration after diagnosis was 59.1±48.5 months. The median overall survival was 153 (range; 1-197) months. Survival was significantly lower in patients with ESRD compared to those without ESRD (p=0.003). On clinical follow up, 48 patients died (9.9%), and 94 patients (19.3%) progressed to ESRD.Conclusion:Clearly defining the etiology of PGN as well as determining the factors leading to ESRD may decrease morbidity and mortality.